ڈاکٹرآنیماری شمل: ایک درخشاں عہد - Mumtaz, Dr. Sohail (Zoraiz, 2023)
In this article, an effort was made to furnish a vivid picture of Schimmel’s life and personality. For this, we focused her childhood, her family background, her teachers and her formal, informal learning at Universities or elsewhere. Besides, her passion for Oriental studies and specifically Islamic learning, Arabic language and Mysticism were thoroughly examined and we also did effort to establish her contact with Sir M. Iqbal and Pakistani Languages. How she was impressed with her teachers and her love for Rumi was given importance. She was used to give lectures on Islam, on its fine arts and Mysticism, world over. She was a glittering personality of twentieth century and she was welcomed by all leading renowned institutions of East and West. People liked to hear her out. With her death, a glittering epoch was ended, unfortunately.